Hubungan Usia Mengalami Menarche dengan Kepercayaan Diri pada Siswi SMA - Frihapma Semita Ade (Psyche 165 Journal, 2020)
This study aims to determine whether there is a relationship between age experiencing of menarche (first menstruation) with the student’s confidence in a high school in Padang. The population of the study was all students at Senior High School 6 Padang. The sampling technique used was proportionate stratified random sampling. The number of samples used was 186 people using a questionnaire that had been tested for its validity and reliability before. The results of this study indicate that the age of menarche has a significant relationship to the confidence of these students. Besides that, the correlation coefficient is negative hence thefaster a person experiences menarche, the lower confidence she will has. The relationship between age of experiencing menarche with self-confidence is significant because the physical and psychological changes that occur after a person experiences menarche can affect one's confidence. Even so, it is not only the age of menarche that is associated with self-confidence, but there are other factors such as the learning process of the environment, family, friends or the community. It is because self-confidence is not a hereditary factor, so that everyone can increase their self-confidence in order to optimize their potential for success